Vibrio splendidus Fur regulates virulence gene expression, swarming motility, and biofilm formation, affecting its pathogenicity in Apostichopus japonicus - Shi, Yue; Liao, Changyu; Dai, Fa; Zhang, Yiwei; Li, Chenghua; Liang, Weikang (Frontiers in Veterinary Science, 2023)
Vibrio splendidus is an opportunistic pathogen, which causes skin ulcer syndrome and results in huge losses to the Apostichopus japonicus breeding industry. Ferric uptake regulator (Fur) is a global transcription factor that affects varieties of virulence-related functions in pathogenic bacteria. However, the role of V. splendidus fur (Vsfur) gene in the pathogenesis of V. splendidus remain unclear. Hence, we constructed a Vsfur knock down mutant of V. splendidus strain (MTVs) to investigate the role of the gene in biofilm, swarming motility and virulence on A. japonicus. The result showed that the growth curves of wild-type V. splendidus strain (WTVs) and MTVs was basically consistent. Compared with WTVs, the significant increase in transcription of virulence-related gene Vshppd mRNA were 3.54- and 7.33-fold in MTVs at the OD600 of 1.0 and 1.5, respectively. Similarly, compared with WTVs, the significant increase in the transcription of Vsm mRNA were 2.10- and 15.92-fold in MTVs at the OD600 of 1.0 and 1.5, respectively. On the contrary, the mRNA level of flagellum assembly gene Vsflic was down-regulated by 0.56-fold in MTVs at the OD600 of 1.0 compared with the WTVs. MTVs caused delayed disease onset time and reduced A. japonicus mortality. The median lethal doses of WTVs and MTVs were 9.116 × 106 and 1.658 × 1011 CFU·mL−1, respectively. Compared with WTVs, the colonisation abilities of MTVs to muscle, intestine, tentacle and coelomic fluid of A. japonicus were significantly reduced. Correspondingly, the swarming motility and biofilm formation in normal and iron-replete conditions were remarkably decreased compared with those of WTVs. Overall, these results demonstrate that Vsfur contributes to the pathogenesis of V. splendidus via regulating virulence-related genes expression, and also affects the swarming and biofilm formation abilities.